Lönsam mjölkproduktion : en fallstudie - Lundberg, Fredrik (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
Ravelsmarks gård have now reached the stage when there are few options for the future. The options are either a construction of completely new farm buildings or a winding up of the milk production. Present on the farm today there is 65 dairy cows plus recruitment. 44 cows stand in long-stalls and 20 cows stand in short-stalls. The objective of this study was to examine the profitability of a completely new cowshed. In order to get costs for investments different milking systems and equipment for feedstuff have been compared. The systems in the investment budget have been chosen on recommendations from advisers, salesmen and on the basis on what is suitable for the farm. One system where a so-called mix feeder wagon is used for the roughage seemed to be best suited for Ravelsmark. The different prices obtained for the manure well show that there are possibilities to decrease the investment costs. By using the rubber cloth from MPG one could save about 300 000 crowns. In the summarizing working plan one can see that the alternative with milking parlour can cope better with decreased milk yield and decreased milk price than the alternative with milk robot. The cost estimates for the robot cannot cope with a milk yield of 9500 litres and a milk price of 2.70 crowns. It differs approximately 200 000 crowns in annual profit between the milking parlour alternative and the robot alternative.